2015
DOI: 10.1007/s12471-015-0651-3
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate use of bioresorbable vascular scaffolds in percutaneous coronary interventions: a recommendation from experienced users

Abstract: Percutaneous coronary interventions (PCI) have become a reliable revascularisation option to treat ischaemic coronary artery disease. Drug-eluting stents (DES) are widely used as first choice devices in many procedures due to their established good medium to long term outcomes. These permanent implants, however, do not have any residual function after vascular healing following the PCI. Beyond this initial healing period, metallic stents may induce new problems, resulting in an average rate of 2 % reinterventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
2
16
0
3
Order By: Relevance
“…A similar observation regarding selection of patients and lesions for BVS implantation has been presented in a few large studies [2, 9]. Patient selection for BVS implantation in this registry was consistent with the main criteria of recommendations from both a European and a Netherlands consensus [14, 15], which indicate the highest beneficial effect on longtime clinical outcome after scaffold deployment. Procedural success depends not only on proper selection of patients but also lesions [16].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A similar observation regarding selection of patients and lesions for BVS implantation has been presented in a few large studies [2, 9]. Patient selection for BVS implantation in this registry was consistent with the main criteria of recommendations from both a European and a Netherlands consensus [14, 15], which indicate the highest beneficial effect on longtime clinical outcome after scaffold deployment. Procedural success depends not only on proper selection of patients but also lesions [16].…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have suggested benefit from intracoronary imaging with IVUS and/or OCT for optimization of PCI results [17]. However, according to the European consensus it is not routinely recommended for this purpose [15]. Intravascular ultrasound is used for the evaluation of the plaque morphology and in the preparation phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in our registry rate of definite ST (2.0% for ACS patients and 2.1% for stable patients) was higher compared to that of currently available metallic DES [35,36]. The importance of patient selection, lesion preparation, pre-and post-dilatation and also the consideration of intra-vascular imaging have to be underlined [37,38]. A pilot imaging study suggested suboptimal implantation as an important cause for BVS ST [28].…”
Section: Discussionmentioning
confidence: 67%
“…As the largest commercially available size of Absorb BVS is 3.5 mm at nominal pressure, the vessel diameter above 4.0 mm should not be targeted because of the risk of extensive malapposition [40]. The device should not be implanted into the lesions that cannot be adequately prepared such as heavily calcified and unsatisfactorily predilatated lesions.…”
Section: Lesion Selectionmentioning
confidence: 99%